2023
DOI: 10.1111/rec.13982
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of key grazing fishes is an important determinant of coral growth and fouling control in coral nurseries

Ewout G. Knoester,
Emilia Rizzi,
Albertinka J. Murk
et al.

Abstract: Restoration is an emerging tool for coral reef conservation, yet despite small‐scale successes there are concerns about high costs and ecological setbacks. Integration between reef ecology and restoration could help address such concerns. A prime example is the use of grazing by herbivores to reduce coral nursery cleaning costs. However, the relation between herbivore communities and cleaning benefits remains unquantified. This study aimed to measure links between herbivorous fish communities, grazing intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Sites with poor benthic state but relatively abundant fish populations could be considered as candidates for restoration (e.g. coral gardening) as part of Target 2, particularly as they have herbivorous fish required to keep algae under control, increasing the likelihood of success (Ladd et al, 2018; Ladd and Shantz, 2020; Gouezo et al, 2021; Knoester et al, 2023). Sites with low fish populations and poor benthic condition may benefit from interventions to reduce threats, including tourism management (under Target 9), pollution reduction (Target 7), and/or fishery and herbivore management (Target 5), depending on the context (see Table S3 for full details).…”
Section: Discussionmentioning
confidence: 99%
“…Sites with poor benthic state but relatively abundant fish populations could be considered as candidates for restoration (e.g. coral gardening) as part of Target 2, particularly as they have herbivorous fish required to keep algae under control, increasing the likelihood of success (Ladd et al, 2018; Ladd and Shantz, 2020; Gouezo et al, 2021; Knoester et al, 2023). Sites with low fish populations and poor benthic condition may benefit from interventions to reduce threats, including tourism management (under Target 9), pollution reduction (Target 7), and/or fishery and herbivore management (Target 5), depending on the context (see Table S3 for full details).…”
Section: Discussionmentioning
confidence: 99%
“…Their study similarly reported that surgeonfish species (Ctenochaetus striatus) consumed the majority of algae on their Coral Tree TM nurseries. However, unlike Knoester et al (2023) where fish biomass differed between fished, reserved and no-take zones, the fish assemblages documented here at Mojo in the Conservation Park Zone (limited hook-and-line fishing) and Rayban in the Marine National Park Zone (no fishing) did not differ in biomass (ANOVA, F = 0.32, P = 0.571), algal consumption (Kruskal-Wallis test, X 2 = 0.66, P = 4.15), abundance (Kruskal-Wallis test, X 2 = 1.71, P = 0.191), or species richness (ANOVA, F = 3.10, P = 0.097; Supplementary Data S4). Schools of Siganus rivulatus, (Surf parrotfish) a family not observed feeding on our CNP nurseries during this study, but known to assist in algal removal on GBR reefs (Fox and Bellwood 2008), have had a major impact on nursery algal reduction in the Seychelles (Shafir and Rinkevich 2010).…”
Section: Fish Biomass and Algal Consumptionmentioning
confidence: 96%
“…While the ecological functions performed by these fish on natural reefs are well-established, their contributions to corals grown on nurseries used for ongoing GBR coral propagation efforts have not been explored (Burkepile and Hay 2008;Green and Bellwood 2009;Bellwood et al 2014). In this study, we test the extent to which assemblages of larger fish (>2.5 cm in length), those known to have the highest contribute to herbivorous fouling removal (Fox and Bellwood 2007;Knoester et al 2019;Knoester et al 2023), facilitate the cleaning of biofouling algae on CNP coral nursery frames. We hypothesised that fish assemblages significantly reduce algal biomass on frames and would thus result in higher coral survivorship (Lirman 2001;McCook et al 2001;Brown et al 2019;Knoester et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation